2013
DOI: 10.1370/afm.1550
|View full text |Cite
|
Sign up to set email alerts
|

Pairing Physician Education With Patient Activation to Improve Shared Decisions in Prostate Cancer Screening: A Cluster Randomized Controlled Trial

Abstract: BACKGROUND Most expert groups recommend shared decision making for prostate cancer screening. Most primary care physicians, however, routinely order a prostate-specific antigen (PSA) test with little or no discussion about whether they believe the potential benefits justify the risk of harm. We sought to assess whether educating primary care physicians and activating their patients to ask about prostate cancer screening had a synergistic effect on shared decision making, rates and types of discussions about pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 33 publications
0
74
0
Order By: Relevance
“…While we have controlled for these factors in our current analyses, these significant demographic differences speak to the larger issue of the need to expand the availability and usability of web-based decision aids for groups who may not have access to this information. Previous studies have shown evidence that incorporating web-based decision aids into primary care appointments can improve rates of decision aid use [25,27,41].…”
Section: Original Researchmentioning
confidence: 99%
“…While we have controlled for these factors in our current analyses, these significant demographic differences speak to the larger issue of the need to expand the availability and usability of web-based decision aids for groups who may not have access to this information. Previous studies have shown evidence that incorporating web-based decision aids into primary care appointments can improve rates of decision aid use [25,27,41].…”
Section: Original Researchmentioning
confidence: 99%
“…The relationship between activation and SDM preferences is underinvestigated, but preliminary evidence suggests that activating patients can increase SDM (Wilkes et al, 2013). Activated patients seek more health-related information and are more knowledgeable about health care (Butler, Farley, Sleath, Murray, & Maciejewski, 2012;Fowles et al, 2009;Harvey, Fowles, Xi, & Terry, 2012).…”
mentioning
confidence: 99%
“…There have been relatively few studies using a Web-based intervention to promote cancer screenings. Most of these are clinic-based interventions that have focused on colorectal cancer screening [20][21][22] and prostate cancer screenings [23,24]. Despite its value in health education, Web-based educational interventions to improve women's BC screening uptakes have not been conducted with KA women.…”
Section: Introductionmentioning
confidence: 99%